Patient and Public Involvement in Youth Mental Health Research: Protocol for a Systematic Review of Practices and Impact - Sales, Célia M. D.; Martins, Filipa; Alves, Marisa M.; Carletto, Sara; Conejo-Cerón, Sonia; da Silva, Luis Costa; Čuš, Anja; Edridge, Chloe; Ferreira, Nuno; Hancheva, Camellia; Lima, Esperanca M. A.; Liverpool, Shaun; et al. (Frontiers in Psychology, 2021)
Various health settings have advocated for involving patients and members of the public (PPI) in research as a means to increase quality and relevance of the produced knowledge. However, youth PPI has been an understudied area. This protocol paper describes a new project that aims to summarize what is known about PPI with young people in mental health research. In line with the Preferred Reporting Items for Systematic reviews and Meta-Analyses Statement guidelines we will identify and appraise suitable articles and extract and synthesize relevant information including at least two reviewers at each stage of the process. Results will be presented in two systematic reviews that will describe a) how youth PPI has been conducted (Review1) and b) what impact youth PPI had on the subsequent research and on stakeholders (Review2). To our knowledge, this is the first set of reviews that uses a critical appraisal tool, which is co-developed with children and young people. Findings from this project will provide valuable insights and set out the key steps to adopting adequate PPI methods when involving children and young people in mental health research.